Higher proportion of G2P[4] rotaviruses in vaccinated hospitalized cases compared with unvaccinated hospitalized cases, despite high vaccine effectiveness against heterotypic G2P[4] rotaviruses. (29th March 2014) - Matthijnssens, J.; Zeller, M.; Heylen, E.; De Coster, S.; Vercauteren, J.; Braeckman, T.; Van Herck, K.; Meyer, N.; Pirçon, J.‐Y.; Soriano‐Gabarro, M.; Azou, M.; Capiau, H.; et al.
Abstract The overall vaccine effectiveness of the monovalent rotavirus vaccine in an observational, prospective, multicentre, hospital‐based case–control study in Belgium (RotaBel) was 90%. However, rotavirus genotype and co‐infecting pathogens are important parameters to take into account when assessing vaccine effectiveness. In this study we specifically investigated the effect of rotavirus genotypes and co‐infecting pathogens on vaccine effectiveness of the monovalent vaccine. In addition, we also investigated the effect of co‐infecting pathogens on disease severity. From February 2008 to June 2010 stool samples of rotavirus gastroenteritis cases of a random sample of 39 Belgian hospitals were collected and subsequently genotyped. Fisher's exact tests were performed to investigate the relationships between rotavirus genotype, co‐infecting pathogens and disease severity. The vaccine effectiveness of a full series of the monovalent rotavirus vaccine against hospitalized rotavirus gastroenteritis caused by G1P[8] rotavirus strains was 95% (95% CI 77.5–98.7). Against G2P[4], the vaccine effectiveness was 85% (95% CI: 63.7–93.8). G4P[8]‐ and G3P[8]‐specific vaccine effectiveness was 90% (95% CI 19.2–98.7) and 87% (95% CI −5.2 to 98.4), respectively. A post‐hoc analysis showed that the genotype distribution was significantly related to the vaccination status (p <0.001), whereby G2P[4] strains were proportionally more prevalent in vaccinated cases than in unvaccinated cases. No statistical associations were found between co‐infection status and vaccination status, Vesikari severity score or rotavirus genotype. The high vaccine effectiveness against the individual genotypes implies robust protection of the monovalent rotavirus vaccine against hospitalized rotavirus gastroenteritis caused by the major human rotavirus genotypes. The prevalence of G2P[4] requires continued monitoring.